Paralomis ceres Macpherson 1989 - Tiwari, Shivam; Padate, Vinay P.; Venugopalan, Vishnu K.; Cubelio, Sherine Sonia; Takeda, Masatsune (Zenodo, 2022)
Paralomis ceres Macpherson, 1989 (Figs. 2–5, Tab. 1) Paralomis ceres Macpherson 1989: 117, figs. 1, 2.— Kazmi & Siddiqui 2006: fig. 6.— Ahyong 2010: 108 (list).— Hall & Thatje 2010: 520 (list, Appendix 1), fig. 15A.— McLaughlin et al . 2010: 13 (list). Material examined. Three females (IO /SS/ANO/00047; PCL 79.0 mm, CW 81.0 mm, PCL 81.0 mm, CW 84.1 mm, PCL 91.0 mm, CW 95.0 mm), Arabian Sea, FORVSS stn. 31609, 8.41°N, 75.89°E, 1237–1245 m depth, HSDT (CV), coll. Dr. Vinu Jacob, 17 July 2013. One male (IO /SS/ANO/00122; PCL 96.8 mm, CW 101.8 mm), Arabian Sea, FORVSS stn. 39901, 8.64°N, 76.10°E, 1065 m depth, HSDT (CV), coll. Dr. Aneesh Kumar K. V., 23 September 2020. Description. Carapace sub-pentagonal, PCL subequal to CW; regions distinct (Figs. 2A, C, 3A). Surface and margins uniformly covered mostly with rounded papilliform tubercles bearing a crown of thin, stiff setae (Fig. 3A– B, D–F); elongated tubercles on carapace include 1 at anterior end of each branchial region; coalesced tubercles on carapace include 1 anterior median and 1 pair of posterior submedians on gastric region, 1 anterior and 1 posterior on each branchial region, and 2 submedian pairs on cardiac region; cervical groove distinct. Pterygostomian region tapering anteriorly, anterior margin with prominent conical spine bearing thin, stiff setae; surface of anterior third covered with smaller, well-spaced minute rounded tubercles, posterior two-thirds covered with relatively closely spaced larger rounded tubercles (Fig. 3D). Rostrum trispinous, 0.1 PCL; broad basally, median spine elongate conical, gently curved upwards, ventral lobe bluntly triangular, covered with granules; dorsal spines short conical, directed obliquely upwards (Fig. 3B). Posterior orbital margin concave, sharply granular; outer orbital spine slender, directed anteriorly, not extending to posterior corneal margin. Anterolateral spine conical, shorter than outer orbital spine; distance between outer bases of anterolateral spines of both sides 0.3–0.4 CW. Ocular peduncle longer than cornea, with sharp granules dorsally, anterior 7 granules spiniform, arranged in arcuate row above cornea, median spine longest, overreaching cornea by more than half length of cornea (Fig. 3C). Antennular peduncle unarmed, reaching anteriorly beyond apex of antennal peduncle by full length of distal antennular peduncle article (Fig. 4B). Basal antennal article covered dorsally with scattered granules, anterolateral corner with curved spine followed by two spiniform granules. Article 2 dorsally and laterally granular, lateral granules spiniform; distolateral spine elongated, overreaching apex of article 4. Article 3 ventrally with irregular row minute granules (Fig. 4B). Scaphocerite a long slender spine distinctly overreaching distal peduncular article, bearing 5 mesial and 5 lateral spines, 4 short spines and 3 or 4 granules dorsally, irregularly granular ventrally (Fig. 4C). Article 4 unarmed, about half length of article 5 (Fig. 4B). Abdominal somite 2 covered with rounded tubercles similar to carapace (Figs. 2C, 3E). Somites 3–6 covered with rounded tubercles progressively smaller in size, margins spinulate, marginal plates subdivided into smaller plates (Fig. 2B, D). Somite 6 1.2 times longer than wide in male, 1.3 in females. Telson bluntly triangular, slightly wider than long, with 1 submedian pair of spiniform granules in addition to tubercles (Fig. 2B, D). Maxilliped 3 pediform, widely separated basally (Fig. 4D). Ischium with crista dentata consisting of 16 teeth; accessory tooth present. Merus, carpus with single row of setae on mesial margin. Propodus triangular in crosssection, with thick bunches of grooming setae on mesial margin, outer base of triangle with row of setae. Dactylus flattened with thick bunches of grooming setae along mesial margin. Chelipeds unequal in both sexes, covered with well-spaced rounded tubercles (Fig. 2A, C). Coxae minutely tuberculate, mesial margins with dense tufts of setae (Figs. 2B, D, 4A). Ischiobasis with tufts of setae on mesial surface, larger tubercles bearing setal tufts. Merus with conical tubercles on lateral surface and dorsal margin, dorsal margin with 4 subdistal progressively smaller spines (Fig. 5A). Carpus with 1 row of spines on dorsal margin, fourth spine longest, mesial margin with large spine (Fig. 5A). Propodus with 1 pair of distal spines followed by 3 spines on dorsal margin, largest spines bearing setal tufts; mesial and lateral surfaces with tubercles bearing setal tufts anteriorly, extending onto proximal portion of pollex (Fig. 5A–B). Dactylus and pollex with conical tubercles proximally (Fig. 5A–B). Major cheliped 1.5 PCL in male, 1.1–1.2 PCL in females; upper palm length 0.9 times height in male, 0.9–1.1 in females; occlusal margins of fingers corneous for distal fourth, proximally with 3 calcareous nodules, proximal nodule largest; dactylus dorsal margin broadly convex, with tufts of golden setae and small proximal spine (Fig. 5A–B), 1.1 times longer than dorsal margin of palm in both sexes. Minor cheliped 1.4 PCL in male, 1.0–1.1 PCL in females; upper palm length 0.9 times height in male, 1.0– 1.1 in females; occlusal margins of fingers corneous for more than distal half, proximally crenulate; dactylus dorsal margin broadly convex, with tufts of golden setae and small proximal granule (Fig. 5C), 1.9 times longer than dorsal margin of palm in male, 1.4–1.7 in females. Pereopods 2–4 similar, elongate, covered with well-spaced small tubercles (Fig. 5D–F). P3 longest. Coxae with setose rounded tubercles. Ischiobasis with distinct conical tubercles, distal ones larger. Merus triangular in crosssection; dorsal and ventral surfaces with small rounded tubercles, flexor surface with short conical spines, extensor surface with a row of 8–10 spines. Carpus with small rounded tubercles on dorsal and ventral surfaces, flexor margin with short conical setose tubercles, extensor margin with 5–7 spines. Propodus with small rounded tubercles on dorsal and ventral surfaces, flexor margin with 10–11 spines, extensor margin with 11–13 spines. Dactylus gently curved, laterally compressed, longer than carpus and extensor margin of propodus (Fig. 5G); flexor margins of male with 12, 13, 16 fixed corneous spines, respectively; 13, 16, 15 spines in smallest female, 15, 12, 12 in medium-sized female, and 17, 15, 15 in largest female; extensor margins of P2, P3 and P4 with 4, 5, 5 proximal spines in male, 4, 5, 5 in smallest female, 5, 5, 7 in medium-sized female and 4, 4, 4 in largest female; apex corneous. Pereopod 2 length 2.2 PCL in male, 1.4–1.5 PCL in females. Merus 0.7 PCL in male, 0.4 PCL in females; length: height ratio 3.7 in male, 2.4–2.8 in females. Carpus 0.6 merus length in male, 0.7–0.8 in females. Propodus 0.8 merus length in both sexes; length: height ratio 4.4 in male, 3.4–3.5 in females. Dactylus 1.1 propodus length in both sexes. Pereopod 3 length 2.2 PCL in male, 1.5 PCL in females. Merus 0.7 PCL in male, 0.5 PCL in females; length: height ratio 3.7 in male, 2.5–2.7 in females. Carpus 0.6 merus length in male, 0.7 in females. Propodus 0.8 merus length in male, 0.8–0.9 in females; length: height ratio 4.7 in male, 3.3–4.1 in females. Dactylus 1.0 propodus length in male, 1.0– 1.1 in females. Pereopod 4 length 2.2 PCL in male, 1.5 PCL in females. Merus 0.6 PCL in male, 0.4 PCL in females; length: height ratio 3.8 in male, 2.7–2.8 in females. Carpus 0.6 merus length in male, 0.7 in females. Propodus 0.9 merus length in male, 0.8–0.9 in females; length: height ratio 4.7 in male, 3.5–3.9 in females. Dactylus 1.1 propodus length in both sexes. Genetic data. COI sequence GenBank accession number: MW291128. 16S rRNA GenBank accession number: MW362253. Remarks. Paralomis ceres was originally described by Macpherson (1989) based on a male specimen (BMNH 1989.926) from off Oman in the Arabian Sea during the John Murray Expedition and deposited in the British Museum of Natural History. A distinctive feature of this species originally recognised in the type description is the carapace dorsal surface being thickly covered with rounded granules of varying sizes (Macpherson 1989: figs. 1, 2A, B). Hall & Thatje’s (2010) comparative study of carapace ornamentation in lithodids standardized the description to “several rounded tubercles with a roughly defined ring of single setae towards the top. It has conical lateral spines or tubercles, which have many setae towards their base”. The morphological description and illustrations of the holotype were found to be adequate for comparison with the present material. The present specimens agree with the description and resemble the illustrations of the holotype in the shape and ornamentation of the carapace, chelipeds and pereopods as well as the armature on the antennal scaphocerite. However, the present specimens exhibit higher P4 length/PCL ratio of 2.2 in the male, 1.5 in the females [vs. 1.5 in the holotype]; P4 merus length: width ratio of 3.8 in the male, 2.7–2.8 in the females [vs. 2.7 in the holotype]; P4 carpus length/merus length of 0.6 in the male, 0.4 in the females [vs. 0.5 in the holotype]; P4 propodus length/merus length ratio of 0.9 in the male, 0.8–0.9 in the females [vs. 0.8 in the holotype]; P4 propodus length: width ratio of 4.7 in the male, 3.5–3.9 in the females [2.4 in the holotype]. The variations between the holotype and the present male specimen appear to be allometric in nature. Sexual dimorphism was observed particularly in the relative lengths of the thoracic appendages. The male possessed the comparatively massive chelipeds than females, and its minor cheliped with a relatively longer dactylus compared to the latter. Secondly, the male possessed the relatively longer P2–P4 with higher pereopod length/PCL and merus length/PCL ratios and lower carpus length/merus length ratio. Thirdly, the male possessed the relatively slender pereopod meri and propodi as evident by higher length/width ratios compared to the females. This species resembles P. dofleini Balss, 1911, P. haigae Eldredge, 1976, P. papua Ahyong, 2020 and P. roeleveldae Kensley, 1981 in the carapace being densely covered with rounded tubercles bearing setae around the apex. However, this species shows the closest resemblance to southwestern Indian Ocean species, P. roeleveldae , in having several rounded tubercles with a ring of short single setae surrounding the apex (Fig. 3F; Hall & Thatje 2010: fig. 15A). In comparison, the western Pacific species, P. dofleini and P. haigae have a thick ring of setae around the apex of the tubercle (Balss 1911: fig. 17 for P. dofleini Hall & Thatje 2010: fig. 15C for P. haigae ); P. papua possesses an uneven ring of setae around the apex of the tubercle (Ahyong 2020: fig. 10D, E). Paralomis ceres shows close affinity with P. papua and P. roeleveldae in the position of the marginal tubercles on the carapace, but these are short and blunt in P. ceres (Figs. 2A, 3A) [vs. long acuminate spines in P. roeleveldae (Kensley 1981: fig. 8A); elongate tubercles in P. papua (Ahyong 2020: figs. 8A, 9A); the absence of anterolateral spines and other prominent marginal ornamentation in P. dofleini (Balss 1911: fig. 16) and P. haigae (Eldredge 1976: fig. 2a, d)]. It shares close resemblance with P. papua in the distomesial cluster of spines on the cheliped merus, mesial spines on the carpus and the prominent spines on the dorsal margin of palm. However, P. ceres differs from P. papua in having a carapace with length subequal to width and a less rounded posterior margin (Figs. 2A, C, 3A) [vs. carapace with length slightly greater than width and an arcuate posterior margin in P. papua (Ahyong 2020: figs. 8A, 9A)], and rounded tubercles on the lateral surface of the cheliped palm (Fig. 5A–C) [vs. conical spines in P. papua (Ahyong 2020: fig. 10A–C)]. Each species possesses a unique number of spines on the antennal scaphocerite: 5 inner and 5 outer spines in P. ceres , 3 or 4 inner and 4 or 5 outer spines in P. papua , 3 inner spines and spinules and 4 outer spines in P. roeleveldae , 14–19 in P. haigae , and 7 in P. dofleini . The ornamentation on the P2–P 4 in P. ceres comprises moderately large spines on the anterior margins of meri, carpi and propodi, and small spines on the posterior margins (Figs. 2A, 5D–F) [vs. large spines on flexor and extensor margins in P. papua (Ahyong 2020: fig. 8A, C) and P. roeleveldae (Kensley 1981: fig. 8A–B); meri with short spines on flexor and extensor margins, carpi and propodi with moderately large spines on anterior margins in P. dofleini (Balss 1911) and P. haigae (Eldredge 1976: fig. 2a, b)]. Distribution. Arabian Sea off Oman at 1189–1354 m depth (Macpherson 1989); southeastern Arabian Sea off India at 1065 and 1237–1245 m depth (present study). : Published as part of Tiwari, Shivam, Padate, Vinay P., Venugopalan, Vishnu K., Cubelio, Sherine Sonia & Takeda, Masatsune, 2022, Paralomis White, 1856 (Crustacea: Decapoda: Anomura) from India, with morphological variability in Paralomis indica Alcock & Anderson, 1899, pp. 301-329 in Zootaxa 5091 (2) on pages 304-310, DOI: 10.11646/zootaxa.5091.2.4, http://zenodo.org/record/5843678 : {"references": ["Macpherson, E. (1989) A new species of the genus Paralomis (Crustacea, Decapoda, Anomura, Lithodidae) from the Indian Ocean. Scientia Marina, 53 (1), 117 - 120. https: // doi. org / 10.1111 / j. 1463 - 6409.1988. tb 00087. x", "Kazmi, Q. B. & Siddiqui, F. A. (2006) An illustrated key to the Malacostraca (Crustacea) of the Northern Arabian Sea. Part VI. Pakistan Journal of Marine Science, 15 (1), 11 - 79.", "Ahyong, S. T. (2010) The marine fauna of New Zealand: king crabs of New Zealand, Australia and the Ross Sea (Crustacea: Decapoda: Lithodidae). NIWA Biodiversity Memoir, 123, 1 - 194.", "Hall, S. & Thatje, S. (2010) King crabs up-close: ontogenetic changes in ornamentation in the family Lithodidae (Crustacea, Decapoda, Anomura), with a focus on the genus Paralomis. Zoosystema, 32 (3), 495 - 524. https: // doi. org / 10.5252 / z 2010 n 3 a 10", "McLaughlin, P. A., Komai, T., Lemaitre, R. & Rahayu, D. L. (2010) Annotated checklist of anomuran decapod crustaceans of the world (exclusive of the Kiwaoidea and families Chirostylidae and Galatheidae of the Galatheoidea) Part I - Lithodoidea, Lomisoidea and Paguroidea. The Raffles Bulletin of Zoology, Supplement, 23, 5 - 107.", "Balss, H. (1911) Nue Paguriden aus den Ausbeuten der Deutschen Tiefsee-Expedition \" Valdivia \" und der japonischen Expedition Prof. Dofleins. Zoologischer Anzeiger, 38 (1), 1 - 9.", "Eldredge, L. C. (1976) Two new species of lithodids (Anomura, Paguridea, Lithodidae) crabs from Guam. Micronesica, 12, 309 - 315.", "Ahyong, S. T. (2020) First King Crabs from Papua New Guinea (Crustacea: Decapoda: Lithodidae). In: Corbari, L., Ahyong, S. T. & Chan, T. - Y. (Eds.), Deep-Sea Crustaceans from Papua New Guinea. Tropical Deep-Sea Benthos 31. Memoires du Museum national d'Histoire naturelle, Paris, 213, 121 - 140.", "Kensley, B. (1981) The South African Museum's Meiring Naude cruises. Part 12. Crustacea Decapoda of the 1977, 1978, 1979 cruises. Annals of the South African Museum, 83, 49 - 78."]}